Karakteristik Komposit Serat Kulit Pohon Waru (Hibiscus Tiliaceus) Berdasarkan Jenis Resin Sintetis terhadap Kekuatan Tarik dan Patahan Komposit - Fadhillah, Arief Rizki; Setiyabudi, Sofyan Arief; Purnowidodo, Anindito (Rekayasa Mesin, 2017)
The fiber composite of hibiscus's bark is the material that comprises synthetic resin as a matrix and hibiscus's bast fiber as reinforcement. The hibiscus's bast fiber have the excellent potency regarding the strength that is employed as reinforcement. Four types of synthetic resin were used in this study, polyester BTQN 157, bisphenol A LP-1Q-EX, ripoxy R-802, and epoxy. The ratio of mass fractions between fiber and resin was 60:40. The initial treatment of the bast fiber hibiscus was immersed in 6 % of NaOH solution for two hours. The composites were manufactured through vacuum bagging process. Tensile strength and fracture mode of composites were investigated. The fiber composites of hibiscus tree bark with bisphenol A LP-1Q-EX resin has the best tensile strength and epoxy resin have a small fracture area was obtained.